Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Machine learning-assisted smartphone fluorescence sensing for ultrasensitive and point-of-care testing of acid phosphatase - Fusheng Zhong; Jiaming Zhang; Huaxi Ruan; Tonglong Yang; Jinbo Cao; Liangliang Peng; Jinhui Liu; Qingqing Deng; Li Wang (Analytica Chimica Acta, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

Development of a modified CaCl2·6H2O shape-stabilized composite phase change material for the greenhouse soil-cooling system - Fuyu Qin; Runhua He; Lingzhi Zhong; Tao Xu; Jiaming Gao; Ximin Lin; Yi Yang; Weitao Shao (Energy and Buildings, 2026)

Analysis of large deformation characteristics of deep foundation pit at a subway station constructed by the tunnel-before-station method - Jiaming Liang; Wenji Su; Tingjin Liu; Huifeng Wu; Lele Lu; Huashan Zhong; Shuyang Zhou (European Journal of Environmental and Civil Engineering, 2025)

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

Torsional Deformation of Existing Tunnels Induced by Obliquely Undercrossing Shield Tunneling - Jiaming Ou; Xiaochun Zhong; Lisu Sun; Wei Wang (Geotechnical and Geological Engineering, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Nutrient dynamics in the East China Sea: Seasonal changes, budget, and ecological impacts - Xiaosong Zhong; Jiaming Liu; Mengjiao Shi; Xiaotian Liu; Zongqing Lv; Xiangbin Ran (Progress in Oceanography, 2025)

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Tailored amphiphilic polymers enable stabilized biologics in hyperthermal water and freeze-drying process - Xiaowen Liu; Jian Chen; Jiaming Zhong; Fener Chen (Chemical Engineering Journal, 2024)

Revealing the travel community in the integrated system of free-floating bike and metro - Jiaming Zhong; Zhaocheng He; Jiemin Xie (Sustainable Cities and Society, 2023)

MLKL and other necroptosis-related genes promote the tumor immune cell infiltration, guiding for the administration of immunotherapy in bladder urothelial carcinoma - Boqiang Zhong; Youzhi Wang; Yihao Liao; Jiaming Liang; Keke Wang; Diansheng Zhou; Yang Zhao; Ning Jiang (Apoptosis, 2023)
The involvement of necroptosis in the immunosuppressive tumor microenvironment has been established and has been shown to contribute to the growth of pancreatic ductal adenocarcinoma, indicating its role in promoting tumor development. However, the relationship between necroptosis and bladder urothelial carcinoma (BUC) has yet to be fully understood. To shed light on this issue, our study aimed to uncover the impact of necroptosis on immune cell infiltration and immunotherapy response in BUC patients. We conducted an analysis of 67 necroptosis genes to assess their expression and genomic changes across pan-cancer and identified 12 necroptosis genes that are prognostically relevant and associated with immune subtypes and tumor stemness in BUC. Using a public database of 1841 BUC samples, we then performed Unsupervised Cluster Analysis and discovered two distinct necroptotic phenotypes in BUC. These phenotypes showed significant differences in molecular subtypes, immune infiltration patterns, and gene mutation profiles. We confirmed this discovery in BUC through qPCR and WB experiments. To evaluate the impact of necroptosis on prognosis, chemotherapy sensitivity, and immunotherapy response (such as anti-PD-L1), we developed a principal component analysis model called NecroScore. Finally, we validated the effects of RIPK3 and MLKL through a nude mouse transplantation model for BUC. Our study has uncovered that necroptosis plays a role in shaping the tumor immune microenvironment in BUC. The high necroptosis phenotype (Cluster B) was characterized by a higher abundance of tumor immunosuppressive cells and more key biological processes driving tumor progression, while the low necroptosis group (Cluster A) had higher FGFR3 mutations. We found that the infiltration levels of immune cells, including CD8+ T cells, were significantly different between FGFR3 mutated and wild-type (WT) samples. Our results confirmed the reliability of NecroScore as a comprehensive assessment tool for evaluating the immunotherapeutic effect and prognosis of BUC patients, with high NecroScore values favoring basal-like differentiation and lower FGFR3 alterations. We also observed that high expression of MLKL had a significant inhibitory effect on tumor growth and increased neutrophil infiltration in vivo. In our study, we uncovered the regulation pattern of necroptosis in the tumor immune microenvironment of BUC. Additionally, we developed a scoring tool called NecroScore that can be utilized to predict the most suitable chemotherapy and immunotherapy strategy for bladder urothelial carcinoma patients. This tool can effectively guide the chemotherapy and immunotherapy regimens for patients with advanced BUC.

Thrust Characteristics of Ducted Propeller and Hydrodynamics of an Underwater Vehicle in Control Motions - Jiaming Wu; Yizhe Dou; Haiyan Lv; Chenghua Ma; Le Zhong; Shunyuan Xu; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
A numerical technique to simulate the hydrodynamic behavior of ducted propellers attached to an underwater vehicle traveling under the mutually interacting flow fields of the vehicle and the propellers is proposed; the hydrodynamic performance of the propellers and the hydrodynamic loading on the main body of the vehicle when it is in different kinds of motion is investigated numerically. In the research, 3D geometric models of the duct, propeller, and main body of the vehicle are first constructed according to their geometrical features. A computational fluid dynamics (CFD) technique based on the hybrid algorithm of dynamic mesh-nested sliding mesh is applied to solve the Navier–Stokes equations that govern the fluid motion around the duct, propeller, and main body of the vehicle when it is in motion. These equations are solved numerically with the CFD code Fluent. With the proposed numerical simulation technique, the hydrodynamic characteristics of the thrusts generated by the ducted propellers and the loading on the main body in the vehicle system under the mutually interacting flow fields are observed. The results of our numerical simulation indicate that the hybrid algorithm of dynamic mesh-nested sliding mesh can simulate multiple degrees of freedom of motion in underwater vehicle systems. In different motion states, the main body exerts a significant influence on the investigated flow fields; during the vehicle motions, negative wakes are formed on both sides of the main body, which lead to a decrease in the thrusts generated by the propellers on both sides. The thrust of the middle propeller is greater than that of the normal single one because of the obstructing effect in the tunnel caused by the main body.